Effect of Learning Media Quizizz Application of Results Learning Students on The Eyes Islamic Culture History Lesson at MI Nurul Huda Pakis Jaya - Jayid, Ruwaidan; pengelola, pengelola (TABYIN: JURNAL PENDIDIKAN ISLAM, 2024)
This study was designed by the authors to test a theory in assisting the application of quizizz application-based learning media technology, utilizing information technology as a learning media tool in conveying a learning content. It would be better if this quizizz application could be applied at the basic level, not only the middle or upper level who could use the quizizz application. Even in facing the challenges of the times, an educator must be more creative and innovative in educating the nation's children as stated in the objectives of the national education system, namely article 1 paragraph 4. This research aims to help formulate problems related to student learning outcomes in Islamic cultural history class V at mi nurul huda, therefore the authors collaborate with permission to propose a theory testing research study, namely the application of quizizz-based learning media, which is very suitable for students and very interested in doing it, aiming to utilize education-based technology facilitation for student learning outcomes in Islamic cultural history subjects. This study uses a quantitative approach, with the type of research pre-experiment design the one group pretest-posttest design, which is the focus of this experimental research sample which totals 30 respondents. The results of the study, based on the results of the inferential test from calculating the hypothesis test that, a significant value of 0.00 <0.05 is produced, meaning that there is an average difference between the pretest and posttest of the effect of the quizizz application of learning media on learning outcomes. Therefore it can be concluded that Ha is accepted and H0 is rejected, which means that there is an influence on the learning outcomes of students in class V Islamic cultural history at Min Nurul Huda Pakis Jaya.